The Actual Structure of eBay's Feedback Mechanism and Early Evidence on the Effects of Recent Changes - Tobias J. Klein; Christian Lambertz; Giancarlo Spagnolo; Konrad O. Stahl (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2007)
eBay's feedback mechanism is considered crucial to establishing and maintaining trust on the world's largest trading platform. The effects of a user's reputation on the probability of sale and on prices are at the center of a large number of studies. More recent theoretical work considers aspects of the mechanism itself. Yet, there is confusion amongst users about its exact institutional details, which also changed substantially in the last few months. An understanding of these details, and how the mechanism is perceived by users, is crucial for any assessment of the system. We provide a thorough description of the institutional setup of eBay's feedback mechanism, including recent changes to it. Most importantly, buyers now have the possibility to leave additional, anonymous ratings on sellers on four different criteria. We discuss the implications of these changes and provide first descriptive evidence on their impact on rating behavior.
urn:nbn:de:bvb:19-epub-13332-3
Keywords: D44; L15; L86; 330; eBay; reputation mechanism; strategic feedback behavior; informational content; reciprocity; fear of retaliation